Labor market pooling and occupational agglomeration - Todd M. Gabe; Jaison R. Abel (Federal Reserve Bank of New York, 2010)
This paper examines the micro-foundations of occupational agglomeration in U.S. metropolitan areas, with an emphasis on labor market pooling. Controlling for a wide range of occupational attributes, including proxies for the use of specialized machinery and for the importance of knowledge spillovers, we find that jobs characterized by a unique knowledge base exhibit higher levels of geographic concentration than do occupations with generic knowledge requirements. Further, by analyzing co-agglomeration patterns, we find that occupations with similar knowledge requirements tend to co-agglomerate. Both results provide new evidence on the importance of labor market pooling as a determinant of occupational agglomeration.
Keywords: R12; J24; R20; 330; Agglomeration; occupations; labor market pooling; knowledge